HPV and coronary diseases in menopausal women: an integrative review - Andrea de Neiva Granja; Andressa Bianca Reis Lima; Paulo Victor Brito Martins; Bernardete Jorge Leal Salgado; Rui Miguel Gil da Costa; Haissa Oliveira Brito; Natalino Salgado Filho (Revista Brasileira de Ginecologia e Obstetrícia, 2024)
Abstract High-risk human papillomavirus (HPV) infection is associated with cervical cancer while low-risk HPV strains mostly cause benign lesions. Multiple studies have also associated HPV with coronary artery (CAD) disease in women. Furthermore, the climacteric period in women, triggers chronic inflammation and has major implications for CAD and associated lipid disorders. The association of HPV with coronary artery disease in climacteric women has few studies, and the objective of this review is to gather and analyse scientific data on the subject. This is an integrative review performed on PubMed and Google Scholar using the keywords “HPV”, “coronary heart disease” and “climacteric”, among these keywords the boolean operator AND and the publication date filter. (2018 onwards). Five articles were found, whose main results show presence of high-risk vaginal HPV in climacteric women. Climacterium and HPV were associated with a three-fold increased risk of CAD, as well as with factors related to menopause that promote atheroma formation, lipid disorders and chronic inflammation. Thus, these results support the association between HPV infection and CAD in climacteric women, possibly via chronic inflammation, hormonal factors related to menopause and dyslipidemia.